Formulasi Losion Ekstrak Kopi Robusta (Coffea canephora) sebagai Penangkal Radikal Bebas: Lotion Formulation of Robusta Coffee Extract (Coffea canephora) as a Free Radical Antidote - Mulana, Farid; Syaubari; Afifah, Syarifah Nur; Lestari, Indah Tri (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2023)
Hand body lotion is a cosmetic used to moisturize skin in order to reduce dehydration. The coffee extract contains bioactive compounds that can provide high antioxidant activation. The purpose of this research is to study the effect of concentration on coffee extract and the addition of olive oil on organoleptic, hedonic, pH, and dispersive properties and to determine the value of the Sun Protection Factor (SPF) in the lotion. The research method involved extracting coffee grounds, heating the oil and water phases to 65°C, and mixing the two phases till it becomes an emulsion. Then add the oil and water to the mixture. The lotion that’s already in the container is ready for testing. This research used 8 formulas with coffee extract concentrations of 2% and 4%, and variations of olive oil from 0, 1, 2, and 3%. Organoleptic and hedonic tests were tried out on 25 respondents for 2 weeks. The pH test was carried out using a universal indicator. The spreadability test was carried out using a petri dish and the SPF test using a UV-visible spectrophotometer. The results showed that 25 respondents preferred formula 4 over the rest, which was white in color, thick in texture, soft scent and the aftertaste was moisturizing. All formulas have good spreading ability and all in the pH range of 5 – 8. The SPF test results were obtained for each formulation in the range of 6.78 – 12.95 and the highest SPF value was owned by F8 of 12.95.